OPTIMALISASI POTENSI WAKAF HIJAU SEBAGAI PLATFORM EKOSISTEM DIGITAL INOVATIF UNTUK MENANGGULANGI DEGRADASI LINGKUNGAN DAN MENDORONG TRANSFORMASI GREEN ECONOMY BERKELANJUTAN - Riadhi, Ahmad Agung (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstrak : This study aims to examine the potential of green waqf as an innovative digital platform to support sustainable green economic transformation. The method used is a descriptive qualitative approach with a literature review approach, utilizing secondary data from scientific journals, policy documents, and academic publications over the past five years. The results show that green waqf contributes to the three main pillars of the green economy: environmental, social, and economic. The digitization of waqf through technologies such as blockchain and crowdfunding has been shown to increase efficiency, transparency, and public participation. The findings also indicate opportunities for integrating digital green waqf into national policies such as the RPJMN (National Medium-Term Development Plan) and the National Development Planning System (SNPRK). The study's conclusions confirm that digital waqf has strategic potential as an Islamic social financing instrument that supports sustainable development. This study recommends the development of a digital green waqf platform and further empirical data-based studies to test the effectiveness of its implementation. Keywords: green waqf, waqf digitization, green economy, sustainable development, blockchain, crowdfunding. Abstrak: Penelitian ini bertujuan untuk mengkaji potensi wakaf hijau sebagai platform digital inovatif dalam mendukung transformasi ekonomi hijau berkelanjutan. Metode yang digunakan adalah kualitatif deskriptif dengan pendekatan studi pustaka, menggunakan data sekunder dari jurnal ilmiah, dokumen kebijakan, dan publikasi akademik lima tahun terakhir. Hasil penelitian menunjukkan bahwa wakaf hijau berkontribusi terhadap tiga pilar utama green economy: lingkungan, sosial, dan ekonomi. Digitalisasi wakaf melalui teknologi seperti blockchain dan crowdfunding terbukti meningkatkan efisiensi, transparansi, dan partisipasi publik. Temuan juga menunjukkan adanya peluang integrasi wakaf hijau digital dalam kebijakan nasional seperti RPJMN dan SNPRK. Kesimpulan penelitian menegaskan bahwa wakaf digital memiliki potensi strategis sebagai instrumen pembiayaan sosial Islam yang mendukung pembangunan berkelanjutan. Penelitian ini merekomendasikan pengembangan platform wakaf hijau digital dan studi lanjutan berbasis data empiris untuk menguji efektivitas implementasinya. Kata Kunci: wakaf hijau, digitalisasi wakaf, green economy, pembangunan berkelanjutan, blockchain, crowdfunding